Characteristics of Biofoam Cups Made from Sugarcane Bagasse with Rhizopus oligosporus as Binding Agent - Eti Indarti; Sri Muliani; Dewi Yunita (Advances in Polymer Technology)
This study is aimed at producing a biofoam cup made from sugarcane bagasse with tempeh mold (Rhizopus oligosporus). Soybean flour (SF) was added to promote the growth of mycelia, which could bind the bagasse fiber matrix. The main materials were whole bagasse (B) and depithed bagasse (DB). The SF weight ratios to bagasse were 1 : 1 (SF1) and 1.5 : 1 (SF1.5). Therefore, the studied specimens were labeled B-SF1, DB-SF1, B-SF1.5, and DB-SF1.5. All biofoam cups were analyzed for their physical properties (water absorption and porosity), mechanical properties (puncture and compressive strengths), biodegradability, and thermal properties (thermogravimetric analysis). The lowest water absorption rates were obtained from the B biofoam cups (23%±2.45%) and the SF1.5 biofoam cups (25.83%±5.19%). Both B-SF1 and B-SF1.5 had lower porosity (8.72%±0.88% and 10.77%±1.54%, respectively) than the DB biofoam cups. Moreover, the B biofoam cups had smoother biofoam surfaces, smaller voids, and lower porosity compared with the DB samples. However, the DB biofoam cups showed the highest puncture strength (2.95±0.37 kg cm−2) among all samples. Nevertheless, the B-SF1.5 biofoam cup had the highest compressive strength (3.98±0.39 MPa) and the DB-SF1.5 exhibited the slowest degradation rate (27%±0.7%) after 14 days of soil burial. The highest thermal stability was obtained from B-SF1.5, which had a thermal degradation temperature of 264°C. Overall, B-SF1.5 had the smoothest surface, good thermal stability, and high compressive strength.